Durar Al-Aqood by Al-Maqrizi (d. 845 AH / 1441 AD) as a Model for Stressing the Integrity of Judges in the Era of Corruption - أحمد عليوي صاحب أ.م. د. (lark, 2021)
The study of the judicial system is one of the important studies since the judiciary is one of the pillars of establishing religion and justice among people. The concept of judicial integrity in Islamic law is an ethical value that brings with it several qualities, such as integrity, honesty, chastity. On the other hand, it manifests itself in avoiding evils and suspicions. In the field of judicial work, integrity is considered more than a virtue, it is a necessity and a prerequisite for taking up the job, so the judge must make sure that his behavior on the personal and professional levels is above the level of suspicion, in mind that the personal behavior of the judge affects the image of the entire judicial system in the eyes of the people. In other words, it can be said that integrity supports the litigants ’confidence in the impartiality and objectivity of their judge. The research with the critical method of Taqi al-Din al-Maqrizi in highlighting and demonstrating the integrity of judges era dominated by administrative, political judicial corruption. The research was divided into three axes. The first axis came in describing the state of the judicial institution in the Mamluk era to give a clear picture of the deterioration of the institution. Political interference during that period. As for the second axis, it is the main aspect of the research, where it dealt with a commitment to justice and preventing interference in the judiciary, and the third axis came about commitment to values ​​and ethics, as it is considered a rare phenomenon in that era.